“I Can Only Work So Hard Before I Burn Out.” A Time Sensitive Conceptual Integration of Ideological Psychological Contract Breach, Work Effort, and Burnout - Jones, Samantha K.; Griep, Yannick (Frontiers in Psychology, 2018)
Employees often draw meaning from personal experiences and contributions in their work, particularly when engaging in organizational activities that align with their personal identity or values. However, recent empirical findings have demonstrated how meaningful work can also have a negative effect on employee’s well-being as employees feel so invested in their work, they push themselves beyond their limits resulting in strain and susceptibility to burnout. We develop a framework to understand this “double edged” role of meaningful work by drawing from ideological psychological contracts (iPC), which are characterized by employees and their employer who are working to contribute to a shared ideology or set of values. Limited iPC research has demonstrated employees may actually work harder in response to an iPC breach. In light of these counterintuitive findings, we propose the following conceptual model to theoretically connect our understanding of iPCs, perceptions of breach, increases in work effort, and the potential “dark side” of repeated occurrences. We argue that time plays a central role in the unfolding process of iPCs over time and the nature of employees’ reactions to iPC breach. Further, we propose how perceptions of iPC breach relate to strain and, eventually, burnout. This model contributes to our understanding of the role of time in iPC development and maintenance, expands our exploration of ideology in the PC literature, and provides a framework to understanding why certain occupations are more susceptible to instances of strain and burnout. This framework has the potential to guide future employment interventions in ideology-infused organizations to help mitigate negative employee outcomes.